2011
DOI: 10.1542/peds.2010-1260
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Extended-Release Tablets as Add-on Therapy to Psychostimulants in Children and Adolescents With ADHD

Abstract: OBJECTIVE: To assess the efficacy and safety of clonidine hydrochloride extended-release tablets (CLON-XR) combined with stimulants (ie, methylphenidate or amphetamine) for attention-deficit/hyperactivity disorder (ADHD). PATIENTS AND METHODS: In this phase 3, double-blind, placebo-controlled trial, children and adolescents with hyperactive- or combined-subtype ADHD who had an inadequate response to their stable stimulant reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 18 publications
1
105
0
1
Order By: Relevance
“…[32][33][34][35][36][37][38][39][40] The PGA is a 7-point scale ranging from 1 (no impairments) to 7 (needs 24-hour supervision due to severe impairments). For children who were being treated with stimulant medications, parents were asked to complete rating scales describing their child' s behavior on and off medication (eg, before the medication took effect in the morning).…”
Section: Determination Of Psychiatric Disorders At Timementioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40] The PGA is a 7-point scale ranging from 1 (no impairments) to 7 (needs 24-hour supervision due to severe impairments). For children who were being treated with stimulant medications, parents were asked to complete rating scales describing their child' s behavior on and off medication (eg, before the medication took effect in the morning).…”
Section: Determination Of Psychiatric Disorders At Timementioning
confidence: 99%
“…59 There is good level of evidence provided by meta-analysis of efficacy for atomoxetine. 57,60,61 Extended-release clonidine [62][63][64] and extended-release guanfacine 65,66 are also efficacious options for the treatment of ADHD, alone or in combination with stimulants. Other pharmacologic alternatives evaluated for the treatment of ADHD are modafinil, bupropion, 57 and tricyclic antidepressants, 67 but all of them have showed weaker evidence of efficacy.…”
Section: Efficacy Of Interventionsmentioning
confidence: 99%
“…Clonidine has been helpful in treating sleeping problems in children with ADHD (Plizka, 2007). Trials of long acting clonidine (with and without the use of psychostimulants) have shown that somnolence and/or fatigue are the major sleeprelated adverse effect of treatment (Biederman et al, 2008;Kollins et al, 2011). However, Biederman et.…”
Section: Non-psychostimulant Medications For Adhd and Effects On Sleepmentioning
confidence: 99%